2022
DOI: 10.1186/s12885-022-10447-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cervical cancer screening utilization among women attending health facilities of Dessie town, Northeast Ethiopia

Abstract: Introduction Despite the higher burden of cervical cases, screening programs in highly affected developing countries remained low. This made the disease to be present at an advanced stage which is almost always fatal, causing enormous pain and suffering for the individual and having significant adverse effects on the welfare of their families and community. Thus, this study aimed to assess determinants of cervical cancer screening utilization among women attending health facilities in Dessie To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…This study showed lower cervical cancer screening utilization among HIV-positive women in the 18–30 age group as compared to as compared to women aged 41 and above. This result is in line with previous studies donein Tigray,Ethiopia [ 19 ], Dessie Town, North East Ethiopia [ 20 ], and Addis Ababa, Ethiopia [ 21 ], which revealed that women in the 18–29 age cohort were less likely to access cervical cancer screeningas compared to women in the (40–49) age cohort. A possible explanation may be that younger womendo not have adequate exposure to informationabout cervical cancerscreening, whereas older womenmay have more exposure to health information when visiting health facilities for different services.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed lower cervical cancer screening utilization among HIV-positive women in the 18–30 age group as compared to as compared to women aged 41 and above. This result is in line with previous studies donein Tigray,Ethiopia [ 19 ], Dessie Town, North East Ethiopia [ 20 ], and Addis Ababa, Ethiopia [ 21 ], which revealed that women in the 18–29 age cohort were less likely to access cervical cancer screeningas compared to women in the (40–49) age cohort. A possible explanation may be that younger womendo not have adequate exposure to informationabout cervical cancerscreening, whereas older womenmay have more exposure to health information when visiting health facilities for different services.…”
Section: Discussionsupporting
confidence: 92%
“…This study also showed that women who did not work outside the home wereless likely to utilize cervical cancer screening than women working for the government. This finding is in line with studies conducted in Addis Ababa, Ethiopia [ 17 ] and Dessie Town, North East Ethiopia [ 20 ], which showed that the probability of cervical cancer screening was higher among government employees than among those who were non-employed. A possible explanation for these results is that women who do not work outside the home may not have exposure to information about cervical cancer and its screening from different sources, such as workplaces and work colleagues [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These were a cervical cancer screening campaign assisted by robust technology (43), health education at the coffee ceremony (44) and other settings (45), and 'single-visit approach'/ 'Addis Tesfa Project' (46). Individual and social determinants that encouraged utilization of cervical cancer screening were having symptoms of vaginal bleeding, physician recommendation (47), women having attended formal education and having good knowledge toward cervical cancer screening, a history of sexually transmitted infections (39), a favourable attitude about cervical cancer and screening (48) and higher sexual autonomy (49). Another study involving health workers also identi ed barriers such as low community and provider awareness of cervical cancer, lack of space and equipment to offer screening, and lack of support from leaders (50), social and religious in uence (51).…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%